Empowering College Students: Cultivating Self-Esteem And Emotional Intelligence (Journal of Namibian Studies : History Politics Culture, 2022)
In the dynamic landscape of higher education, the holistic development of college students takes center stage, with a growing emphasis on equipping them not only with academic knowledge but also with essential life skills. Among these, self-esteem and emotional intelligence stand out as pivotal attributes that pave the way for personal growth and success in various spheres of life. This exploration delves into the realm of empowering college students through the deliberate cultivation of self-esteem and emotional intelligence. By nurturing these critical facets, educational institutions embark on a journey to foster well-rounded individuals who possess the inner strength to navigate challenges, forge meaningful relationships, and ultimately thrive in a complex and interconnected world. This investigation delves into the strategies and implications of nurturing self-esteem and emotional intelligence within the context of higher education, shedding light on how such efforts can empower students to become confident, empathetic, and resilient contributors to society. The study concludes that students' overall self-esteem is moderate, indicating a balance between high and low levels. Emotional intelligence varies based on courses, with Psychology and Office Systems Management students having higher levels compared to Tourism and Entrepreneurship students. This difference highlights emotional intelligence's role in effective emotion management. Higher emotional intelligence improves emotion navigation, while lower emotional intelligence hampers emotion understanding. Importantly, self-esteem isn't solely tied to emotion management skills. Positive self-regard doesn't guarantee high emotional intelligence. This study clarifies that self-esteem and emotional intelligence are distinct and not strongly correlated. Enhancing emotional intelligence doesn't solely depend on improving self-esteem, emphasizing their separate nature.